Pengaruh Kepuasan Terhadap Kesetiaan dan Business Builders Wiraniaga Multilevel Marketing Oriflame Surabaya - Ika H., Nuruni (Jurnal Riset Ekonomi dan Bisnis, 2008)
Product of daily need is more day to day. Product wish to take as the fist product. The key to reach as the must delicide any needing and hoping market and they are satisfied. The order side they use multilevel marketing as a business oriflamme industry make direct saving multilevel marketing with cosmetics product, they other no limit in come.The variable are communication satisfaction, margin laba satisfaction, product satisfaction, Loyalty to salesman, Loyalty to product, dan Business builder. Using scale semantic differential as made variable scale. Research population is all of active member of Oriflame multilevel marketing, they have one year or more in. They are 112 of member, I’m using Structural Equation Modeling to analyze the data.I have obtain the output and say they product satisfaction factor have positive influence to loyalty to product, loyalty to product have positive influence to loyalty to salesman and loyalty to product have positive influence the business builders, they are all no acceptance. Next hipotesis say they margin laba satisfaction have positive influence to loyalty to product, margin laba satisfaction have positive influence to loyalty to salesman, communication satisfaction factor have positive influence to loyalty to salesman have positive influence to business builders, they are not acceptanceKeywords: Communication Satisfaction, Profit Margin Satisfaction, Product Satisfaction, Loyalty to Salesman, Loyalty Product, Business Builders